2019
DOI: 10.1186/s13065-019-0523-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioactivity of oxovanadium(IV)tetra(4-methoxyphenyl)porphyrinsalicylates

Abstract: Herein, we report the synthesis of metal complexes of vanadium with heterocyclic tetradentate ligand. Four N atoms of the heterocyclic porphyrin ring occupy the equatorial position and O atom of salicylic acid occupies the axial position in the complex. The thermal and chemical stability of the complexes were assessed by thermogravimetric analysis (TGA). The electrochemical behavior of the designed complexes is also studied using cyclic voltammetry. These complexes were then further evaluated for in vitro anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These values were further confirmed by simulated spectral data and were found to be in good agreement (Table ). The g ∥ < g ⊥ and A ∥ > A ⊥ are arrangements for axially compressed V IV (d xy 1 ) systems. From spin Hamiltonian parameters calculated for complexes V-1 and V-2 , it is clear that both complexes are axially compressed. Similar to vanadium­(IV) porphyrins, in both complexes, there is an absence of super hyperfine splitting from pyrrolic nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…These values were further confirmed by simulated spectral data and were found to be in good agreement (Table ). The g ∥ < g ⊥ and A ∥ > A ⊥ are arrangements for axially compressed V IV (d xy 1 ) systems. From spin Hamiltonian parameters calculated for complexes V-1 and V-2 , it is clear that both complexes are axially compressed. Similar to vanadium­(IV) porphyrins, in both complexes, there is an absence of super hyperfine splitting from pyrrolic nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the biochemical and photo-electro properties of porphyrin have attracted a growing interest. Substituted metalloporphyrins are now playing crucial roles in the fields of iatrology [47], medicinal chemistry, [48][49][50], analytical chemistry [49] and electronic devices [13-15, 51, 52]. It has been observed that when a porphyrin complex is applied in the natural enzyme peroxidase, the dioxygen gets activated under mild conditions therefore, porphyrin complexes with various metal ions have received much attention as antioxidants [53].…”
Section: Synthesis and Characterization Of Metalloporphyrins 1a−d And...mentioning
confidence: 99%
“…Cu(II), Pd(II), Ag(I) and VO 2+ porphyrin metal complexes showed exceptional properties for medicinal and biological applications [47][48][49][50]. While Nickel porphyrin complexes have been employed successfully in catalytic reactions [54].…”
Section: Synthesis and Characterization Of Metalloporphyrins 1a−d And...mentioning
confidence: 99%
“…There are multiple applications for naturally occurring porphyrins and their metal complexes in various research disciplines, including dye degradation, sonodynamic anticancer therapy, photodynamic therapy, , MRI contrast agent, drug delivery, single-cell imaging, and antimicrobial to cancer treatment. VO­(tpps) (Figure b) is a water-soluble insulin-mimetic vanadyl-porphyrin complex for oral therapy of type 1 and type 2 diabetes mellitus in animals. , VO­(tpps) is regarded as an effective insulin-mimetic complex.…”
Section: Introductionmentioning
confidence: 99%